2017
DOI: 10.1016/j.jebdp.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

In Defense of Flossing: Part II-Can We Agree It's Premature to Claim Flossing Is Ineffective to Help Prevent Periodontal Diseases?

Abstract: Periodontal diseases (PD) are complex, multifactorial disorders. Effective daily plaque control promotes gingival/periodontal health. Recent meta-analyses and other reviews have found inconclusive evidence to support that tooth flossing promotes gingival/periodontal health. Ideally, the claim should have been that, “at present, we do not have high-quality evidence from well-designed randomized clinical trials (RCTs) to determine whether flossing lowers the risk for periodontal diseases.” Rather than “not prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In relation to flossing, prior meta data (Cochrane Reviews, etc.) on this topic have not used a reliable and valid measure of oral hygiene skill, such as OHSIM; thus, many studies have relied on self‐reported behavior, which is a weak foundation for evidence‐based dentistry . Future studies, using OHSIM could help generate stronger evidence for claims related to toothbrushing and flossing efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In relation to flossing, prior meta data (Cochrane Reviews, etc.) on this topic have not used a reliable and valid measure of oral hygiene skill, such as OHSIM; thus, many studies have relied on self‐reported behavior, which is a weak foundation for evidence‐based dentistry . Future studies, using OHSIM could help generate stronger evidence for claims related to toothbrushing and flossing efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, PD is currently one of the most pervasive oral complications of human immunodeficiency virus‐positive (HIV+) adults, a group in which poor oral health is common . Exposure to low nadir CD4 (<200 cells/μL) ever can contribute to gingival recession, an important component of PD, which could then complicate plaque control . Deficits in oral health can be especially detrimental for HIV+ adults, as it can interfere with antiretroviral therapy (ART) compliance, reduce nutritional intake, lower self‐esteem, and diminish quality of life, thus, negatively impacting the overall health…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations